Serum and Prostatic Tissue Concentrations of Cefazolin, Ciprofloxacin and Fosfomycin after Prophylactic Use for Transurethral Resection of the Prostate - Annemieke Sobels; Koen J. Lentjes; Frank M. J. A. Froeling; Cees van Nieuwkoop; Erik B. Wilms (MDPI AG, 2022)
The optimal drug of choice, its time of administration and duration of antibiotic prophylaxis in patient undergoing a TURP procedure are still matters of debate. In this study, we evaluated the concentrations of cefazolin, ciprofloxacin and fosfomycin in the human prostate in a cohort of men undergoing TURP. We compared prostate tissue concentrations to the serum concentrations and MICs of common uropathogens, to determine the appropriateness of the current presurgical prophylactic antibiotics and to gain supportive data about the suitability of fosfomycin for antibiotic prophylaxis in men undergoing urological procedures of the prostate. After a single intravenous dose of cefazoline or an oral dose of ciprofloxacin prior to TURP, concentrations in serum and prostate tissue of well above the MIC (EUCAST breakpoint) of common uropathogens (Enterobacterales) were reached, and both antibiotics seem potentially effective in preventing postsurgical infections. A single dose of oral and intravenous administration of fosfomycin both led to serum concentrations above the MIC for uncomplicated urinary tract infections (8 µg/mL). The MIC for other infections (32 µg/mL) was only reached after a single dose of intravenous fosfomycin. We were unable to detect fosfomycin concentrations in prostate tissue.